2014
DOI: 10.1007/s00167-014-3043-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the native ACL insertion site “completely restored” using an individualized approach to single-bundle ACL-R?

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 27 publications
(41 reference statements)
0
34
0
1
Order By: Relevance
“…150 The cross-sectional area of the tibial insertion site is larger than the femoral insertion site. 89,109 The mean length of the ACL is from 18 to 34 mm, but significant individual variations are found in the anatomy both regarding length, thickness and size of the insertion sites. 109 A great variance (18.8 ±10.1 %) of the ligament-length during flexion, extension, and rotation of the knee has been reported.…”
Section: Anatomy Of the Aclmentioning
confidence: 99%
“…150 The cross-sectional area of the tibial insertion site is larger than the femoral insertion site. 89,109 The mean length of the ACL is from 18 to 34 mm, but significant individual variations are found in the anatomy both regarding length, thickness and size of the insertion sites. 109 A great variance (18.8 ±10.1 %) of the ligament-length during flexion, extension, and rotation of the knee has been reported.…”
Section: Anatomy Of the Aclmentioning
confidence: 99%
“…Finally, these results underscore the importance of the current trend towards a more individualized approach to ACL reconstruction . For example, using an 8 mm diameter AM and 6 mm diameter PL graft as originally described may exceed the anatomic center–center spacing for the average patient ( R = 4 mm + R = 3 mm + 2 mm for the bone bridge = 9 mm).…”
Section: Discussionmentioning
confidence: 76%
“…Both systems use tablet-software to wirelessly acquire and analysis the data therefore, the same graft size or reconstruction technique cannot restore the native insertion side in all patients [38]. Recent studies highlighted the increased risk of reconstruction failure with smaller grafts [39] and demonstrate that single-bundle reconstruction surgery restores only 70-79 % of the native ACL insertion side [40]. Several biomechanical studies [41][42][43] as well as randomized clinical trials [44] reported higher antero-posterior and rotational stability in doublebundle reconstructions surgery compared to anatomical single-bundle reconstruction surgery.…”
Section: Anatomic Acl Reconstruction Surgerymentioning
confidence: 99%